THE CHRONICLE: HUMANITY WITH A CERTIFICATE OF EXISTENCE (Andamios, Revista de Investigación Social, 2008)
This article explores the narrative capacity of the chronicle and recognizes its intrinsic ability to tell time, that is, to account for time, and to give to humanity a certificate of existence. The chronicle, as a hybrid genre, is capable of showing life through narrative and this has been the case since centuries ago. An example is the conquest of the Americas and the role of the writer of chronicles in showing the monarch what there was to see in the new world, so the latter, could take possession, in his imagination, of the territories. But the chronicle didn’t stop there. It migrated, according to Walter Mignolo, to other disciplines: to literature and to journalism. And it is relevant to this day in the works of those who work on the plane that doesn’t distinguish reality from fiction. The chronicle is alive and will continue to be a narrative vehicle that saves lives.
Keywords: Chronicles; chronicles of the Indians; time; space; narrative